2006
DOI: 10.1258/rsmsmj.51.4.21
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Alcohol Misuse Among Acute Admissions: Current Experience and Historical Comparisons

Abstract: Alcohol misuse is common amongst acute medical admissions. Since 1979, there has been a particular increase in female medical admissions who misuse alcohol. Medical opinion regarding alcohol misuse lacks sensitivity in identifying at risk individuals compared with a validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We found that the rate of alcohol use problems among Taiwanese elderly aboriginal women is in the high range (25.59%) compared with that of other populations, such as 4.51% for elders in a small Italian town (Di Bari et al ., 2002), 1.8% for the women of Li ethnic minority in villages in Hainan, China (Tang et al ., 2005), 12.2% for Scottish women (Cameron et al ., 2006), 7.4% for adults in Spain (Carballo et al ., 2006), or 16.5% for adults in New Mexico (Woerle et al ., 2007). Therefore, the high prevalence of alcohol use problems among Taiwanese elderly aboriginal women is likely to be associated with their poor sleep quality, depression, and worse physical condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the rate of alcohol use problems among Taiwanese elderly aboriginal women is in the high range (25.59%) compared with that of other populations, such as 4.51% for elders in a small Italian town (Di Bari et al ., 2002), 1.8% for the women of Li ethnic minority in villages in Hainan, China (Tang et al ., 2005), 12.2% for Scottish women (Cameron et al ., 2006), 7.4% for adults in Spain (Carballo et al ., 2006), or 16.5% for adults in New Mexico (Woerle et al ., 2007). Therefore, the high prevalence of alcohol use problems among Taiwanese elderly aboriginal women is likely to be associated with their poor sleep quality, depression, and worse physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years they have faced a new cultural discontinuity and oppression (Ko et al ., 1994), with a high prevalence of substance abuse (Ko et al ., 1994), low socioeconomic status (Ko et al ., 1994; Ralph-Campbell et al ., 2006), and poor general health (Jean-Louis et al ., 2001). The prevalence of women with alcohol problems has increased significantly (Cameron et al ., 2006). Owing to differences in metabolism, women of all ages are at a higher risk than men for negative physical, medical, social, and psychological consequences associated with at-risk and higher levels of alcohol consumption (Epstein et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…GGC has the worst four local authority areas in the UK for male deaths from alcohol and two of the four worst areas for women. 2 Alcohol-related hospital admissions are frequent in Glasgow hospitals 3 with alcohol accounting for 37% of accident and emergency admissions overall and 47% in Glasgow Royal Infirmary, the hospital closest to the City Centre. 4 This compares to 12% of accident and emergency admissions in a study from England (Liverpool).…”
Section: Introductionmentioning
confidence: 99%